Uji Aktivitas Antibakteri Ekstrak Kulit Buah Kawista (Limonia acidissima L.) terhadap Koloni Salmonella sp. Secara In Vitro - Hasanah, Marlia; Ulviani, Ida (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2023)
One of the potential agricultural products that are quite large from Benuatan Village, Belantikan Raya District, Lamandau Regency, Central Kalimantan Province is Kawista fruit. Benuatan residents use Kawista fruit for consumption, both raw and ripe. The large consumption of this Kawista fruit leaves quite an abundance of fruit peels. Based on the results of the phytochemical analysis of Kawista fruit peel extract, there were saponins, tannins, alkaloids, flavonoids, and terpenoids. Another source of income for the Benuatan population in the form of seafood in the form of fresh fish, dried fish and other processed fish is susceptible to contamination by microorganisms, such as Salmonella sp., which are pathogenic in the intestines of animals and humans. This study aims to determine the antibacterial activity of Kawista rind extract on the growth of Salmonella sp. bacteria in vitro, and to determine the effective concentration of Kawista rind extract to inhibit the growth of Salmonella sp. bacteria using the paper disc diffusion method. The type of research used is pure experimental research. Based on the results of the study, obtained data on the diameter of the growth inhibition zone of Salmonella sp. bacteria, using Kawista fruit peel extract variables with concentrations of 12.5%, 25%, 50%, 75%, and 100% with negative controls of distilled water and methanol, as well as control positive for tetracycline. At a concentration of 100% Kawista extract, the diameter of the bacterial inhibition test was the largest and significantly different from the treatment group with concentrations of 12.5%, 25%, 50% and 75%. However, the 100% Kawista extract showed a smaller diameter of bacterial inhibition than the tetracycline treatment group, but not significantly different. In the methanol treatment, the inhibition test for bacterial diameter was greater than that of the Kawista extract treatment group of 12.5%, 25%, 50% and 75%, but not significantly different. Based on the results of the study it can be concluded that, Kawista rind extract is effective for inhibiting the growth of Salmonella sp. bacteria, Kawista rind extract at a concentration of 100% is the most effective for inhibiting the growth of Salmonella sp. bacteria, and shows results not significantly different from tetracycline antibiotics.